2006
DOI: 10.1016/j.scriptamat.2005.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of a dilatometric anomaly previous to the ferrite-to-austenite transformation in a low carbon steel

Abstract: During continuous heating of a cold rolled low carbon (LC) steel a dilatometric anomaly has been detected previous to the well known ferrite-to-austenite transformation. This anomaly is due to the texture change and/or the dislocation annihilation that accompany the recrystallization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Gridnev et al [33] attributed this observation to annihilation of point and line defects as well as microcracks. De Cock et al [10,32] also showed that the reduction in dislocation density during recrystallization can account for the amount of dilation (%0.05 pct) that is observed during heating of 80 pct CR low and ultralow carbon steels before austenitization at 10 K/s. Thus, it is concluded that the deviation from linear thermal expansion is related to recrystallization of the sample during heating and is consistent with the volume change caused by a reduction in the average dislocation density.…”
Section: Appendixmentioning
confidence: 98%
See 2 more Smart Citations
“…Gridnev et al [33] attributed this observation to annihilation of point and line defects as well as microcracks. De Cock et al [10,32] also showed that the reduction in dislocation density during recrystallization can account for the amount of dilation (%0.05 pct) that is observed during heating of 80 pct CR low and ultralow carbon steels before austenitization at 10 K/s. Thus, it is concluded that the deviation from linear thermal expansion is related to recrystallization of the sample during heating and is consistent with the volume change caused by a reduction in the average dislocation density.…”
Section: Appendixmentioning
confidence: 98%
“…Microstructural observations at 873 K (600°C) and 1123 K (850°C) showed that the microstructure changed from the CR to a completely recrystallized one during the first heating stage. Thus, a reduction in dislocation density and texture changes from an alpha fiber to a gamma dominant texture [10,32] that occur during ferrite recrystallization remain as possible explanation for the deviation. A reduction in specific volume of 0.37 pct for 80 pct cold-drawn steel wires during annealing and before austenite formation was reported by Gridnev et al [33] With an assumption of isotropic change in length during dilation, one can estimate DL/ L o through DL/L o % DV/3V o for a small relative volume change in which DL is the length change, L o is the initial length, DV is the volume change, and V o is the initial volume of the sample.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most usual experimental techniques for the in-situ study of phase transformations in steels are differential scanning calorimetry [7] and magnetization measurements [8]; however, dilatometry is probably the most widely used technique [9][10][11][12][13][14][15][16]. There exist semi-empirical models to quantify the progress of ferrite and/or pearlite on cooling [13,14,17].…”
mentioning
confidence: 99%
“…The pole figures (110), (200) and (211) were measured and a series expansion technique was employed to calculate the orientation distribution function (ODF), along with ghost correction [15]. The typical cold rolling and recrystallisation textures of LC steels may be described by two texture fibres: an incomplete α-fibre characterised by <110> parallel to RD; and a complete γ-fibre which comprises all crystals with {111} plane parallel to ND [16].…”
Section: Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%